Design and Build of a 24-hour Open Pharmacy Geographic Information System in Medan City - Siti Emi Triana Pasaribu (IHSA Institute, 2023)
Geographic Information System is an information system that is used to enter, store, retrieve, manage, analyze, and generate geographic or geospatial referenced data, to support decision making in planning. Currently, the terms Desktop GIS, WebGIS and Spatial Database are known. is a manifestation of the development of Geographic Information Systems to provide solutions to various problems that can only be answered with this GIS. Using GIS is expected to make it easier for decision makers to find out the locations of 24-Hour Open Pharmacies in Medan City. Because GIS will describe the location of the 24-hour open pharmacy in the city of Medan. This WebGIS application is made using the PHP programming language and uses the MySql database. In this application only the admin can process data input, edit data, and delete data. Meanwhile, users can only view and search for information about the location of 24-hour open pharmacies in Medan City. The purpose of making this application is to create a system that makes it easy to find out and get accurate information about the location of a 24-hour open pharmacy in the city of Medan. Making this application is expected to be able to provide the best possible information about Pharmacies - Pharmacies Open 24 Hours in the city of Medan. Making this application using Mapserver-based Web programming